Electrical Modernization with Power Management System Implementation for Distributed Power Generation - Anantasate, Sumeth; Chokpanyasuwan, Chaimongkon; Bhasaputra, Pornrapeepat; Pattaraprakorn, Woraratana (ECTI Transactions on Electrical Engineering, Electronics, and Communications, 2009)
When power demand is foreseen to rapidly increase in near future, the need to upgrade the electrical system/ equipment becomes apparent. When operation must proceed while any change is in progress, the revision is very di±cult. Parallel operation of electrical equipment of various vintages and ratings is inevitable for some extent of time. The special considerations and review on the monitoring, metering and control of new master PLC controller called power management system (PMS) are discussed. Electrical distribution system design and equipment modi¯cation and upgrade which improve system operability, enhance reliability and contribute to safety are described. Furthermore, hazard is evaluated for electrical design of a system upgrade. The primary technique for the hazard evaluation was a hazard and operability study, which is a brainstorming approach conducted by a multidisciplinary team. The approach simulates creativity of the team member to generate new ideas. As a result of this study, numerous and qualitative recommendations have been made to electrical design the safety and operability problem out of the major power system upgrade. Among the recommendations are suggestions on protection and control strategy, materials of construction, process material releases, alternative design options, and maintenance of this power system upgrade.